Don't push too many trolleys : and other tips from navigating life and business - Tan, Ying, 1975- (John Wiley & Sons, Ltd., 2021)
"Tips from the Trolley Boy is a book for anyone, from any walk of life, at any stage of life. It contains some of the most straightforward and applicable advice you've ever heard. Simple principles to apply to life are given in an accessible and friendly voice. Ying Tan's approachable, caring personality infuses this book with warmth. He is as likeable in print as he is in life (as readers will learn from the outstanding testimonials given by the people who work for him). In the initial chapters, Ying introduces himself and shares a little about his background, including some of the history of his parents and Chinese ancestors. He then outlines his business journey from Investment Banking intern to CEO of a multi-billion financial services company -- touching on his ups and downs, especially through the global economic crash of the last decade -- and goes on to describe, in each chapter, the ten most important principles he personally applies to his life. These are well structured, one flowing naturally into the next. Finally, Ying share his hopes and dreams for the future, and includes some comments from his team who talk of how inspiring their boss has been to them over the years"--